Effect of Leverage, Profitability and Firm Size on Financial Distress (Empirical Study on Transportation Companies Listed on the Indonesia Stock Exchange 2016 –2020) - Liandra Andika; Nuryaman Nuryaman (Budapest International Research and Critics University, 2022)
The impact of the Covid 19 outbreak is very devastating for the economy in Indonesia and also the world, one of which is affected is transportation companies. Transportation companies are affected by physical distancing or social distancing which is now chosen as a government policy. The purpose of this study was to determine the effect of leverage, profitability, and firm size on financial distress either partially or simultaneously. The population in this study are transportation companies listed on the Indonesia Stock Exchange in 2016-2020. The technique used in determining the sample in this study is purposive sampling. After the data criteria have been determined, the number of samples used in this study amounted to 11 companies in the transportation sector. Hypothesis testing using multiple linear regression analysis, F test, t test and coefficient of determination (R2). The results showed that leverage and firm size partially positive effect on financial distress, while profitability has a significant negative effect on financial distress. And lastly, everage, profitability and firm size simultaneously have a significant effect on Financial Distress with a 33 percent contribution.